TECNOLOGIA DIGITAL E EDUCAÇÃO: O CONTEXTO DO USO DE DISPOSITIVOS MÓVEIS PARA APRENDIZAGEM NO ENSINO FUNDAMENTAL II EM UMA ESCOLA PÚBLICA DE SANTARÉM - PARÁ - TAPAJÓS, Manuela Patricia Porto (Universidade Federal do Oeste do Pará, 2022)
The changes, which are increasingly accelerated in the various social sectors, are a hallmark of today's society. The school, as an institution that belongs to this society, also suffers influences and mutations, mainly due to the advances in Information and Communication Technologies (ICTs). In this sense, ICTs have occupied classroom spaces as a proposal for innovation in teaching and learning processes. Thus, understanding the context of the practices and relationships of students and teachers, specifically with mobile technology and the smartphone, is the scope of this research. Accordingly, we propose to verify and understand whether or not these digital technologies interfere in the technology-teacher-student relationship in the classroom environment. It is a qualitative study, in which we resort to literature review through systematic review, documentary and empirical research. The instruments for data collection were: two questionnaires (one for teachers and another for 9th grade students), direct observation, without interference from the researcher, observation field diary. The research participants were students and teachers of the 9th grade of elementary school in a school in the urban area of the municipal network of the city of Santarém-Pará. As for the results: i) the students participating in the research corroborate the PNAD-Continuous study (2017), regarding the great use of the smartphone, connected in chat, social network and games applications; ii) use applications, when requested by the teacher, through the mobile connection, which was occasionally shared between those involved, since access to broadband internet is still a challenge in our city; iii) the use of these devices is distorted from the teacher's proposal, since some students did not opt for employment within the teaching and learning processes, in which the didactic sequence was not successfully completed by the teacher, due to interferences and deviations; iv) difficulties and teacher resistance regarding the practices combined with the technological resources available on the smartphone, whether due to the choice of traditional education, the precarious internet connection, the dispersion of students regarding the use of the device or because they do not feel prepared to perform activities that involve digital technologies. In contrast, there are teachers who promote mechanisms in their activity in which the smartphone appears as a means to achieve a final goal. Thus, the context investigated revealed to us that the practices and relationships of students and teachers with digital technologies in the classroom are linked to infrastructure, training and effective involvement issues of those who make up the community school